PELAYANAN STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG PADA SISWA BUNDA MULIA SCHOOL JAKARTA UTARA - Pambudi, Wiyarni; Aqila, Fitri; Natalia, Desi (Jurnal Bakti Masyarakat Indonesia, 2023)
Successful indicators of fostering child growth and development are not only improving children's health and nutritional status but also developing children's mental, emotional, social and independence optimally. Early detection of growth and development deviations needs to be carried out in order to find out the possibility of deviations including following up on any parents' complaints about child development problems. The service of Stimulation, Detection, Early Intervention for Growth and Development (SDIDTK) was provided to 65 (87.8%) students of Bunda Mulia School, involving clerkship students of the Resident Program for anthropometric examinations in the form of measuring body weight and height. Parents of students were asked to cooperate in filling g-form questions with the Developmental Pre Screening Questionnaire (KPSP) and the Emotional Behavior Problem Questionnaire (KMPE). Assessment of examination data shows the status of individual growth and development, which needs to be followed by stimulation or intervention ef orts according to the needs of each child. Growth screening showed 58 ( 89.2%) of students had good nutritional status, although there were still students with overweight status, obesity, and short stature. Developmental screening found 55 (93.2%) students with age-appropriate KPSP assessments and 50 (84.7%) results KMPE is normal. Clean and healthy living habits include feeding rules, dental and oral health care, prevention of Influenza Like Illness-Severe Acute Respiratory Infection (ILI-SARI), hearing, vision and daily sleep patterns are not yet fully can be applied well by Playgroup, Pre-Kindergarten, Kindergarten-1, and Kindergarten-2 students. ABSTRAK Indikator keberhasilan pembinaan tumbuh kembang anak tidak hanya meningkatnya status kesehatan dan gizi anak tetapi juga mental, emosional, sosial dan kemandirian anak berkembang secara optimal. Deteksi dini penyimpangan tumbuh kembang perlu dilakukan guna mengetahui adanya kemungkinan penyimpangan termasuk menindaklanjuti setiap keluhan orang tua terhadap masalah tumbuh kembang anak. Pelayanan Stimulasi, Deteksi, Intervensi Dini Tumbuh Kembang (SDIDTK) diberikan kepada 65 (87,8%) siswa Bunda Mulia School, melibatkan mahasiswa kepaniteraan Program Studi Profesi Dokter untuk pemeriksaan antropometri berupa pengukuran berat badan dan tinggi badan. Orangtua siswa diminta kerjasamanya mengisi g-form pertanyaan Kuesioner Pra Skrining Perkembangan (KPSP) dan Kuesioner Masalah Perilaku Emosional (KMPE). Asesmen data pemeriksaan menunjukkan status pertumbuhan dan perkembangan secara individual, yang perlu diikuti upaya stimulasi atau intervensi sesuai kebutuhan masing-masing anak. Skrining pertumbuhan menunjukkan 58 (89,2%) siswa berstatus gizi baik, walaupun masih dijumpai siswa dengan status gizi lebih, obesitas, dan perawakan pendek. Skrining perkembangan mendapati 55 (93,2%) siswa dengan asesmen KPSP sesuai usia dam 50 (84,7%) hasil KMPE normal. Kebiasaan perilaku hidup bersih dan sehat antara lain aturan makan (feeding rules), perawatan kesehatan gigi dan mulut, pencegahan Influenza Like Illness-Severe Acute Respiratory Infection (ILI-SARI), daya dengar, daya lihat dan pola tidur harian belum sepenuhnya dapat diterapkan dengan baik oleh siswa Playgroup, Pre-Kindergarten, Kindergarten-1, dan Kindergarten-2.